COLONEL OF THE RUSSIAN ARMY M. KOTZEBUE ON THE JARO-BELOKAN SOCIETIES - Aliev, Bagomed Gadaevic (History, Archeology and Ethnography of the Caucasus, 2018)
The paper is devoted to the historiographic analysis of the information of Colonel of the Russian Army Kotzebue on the Jar-Balakan. The work raises almost all questions of socio-economic development and administrative and political structure of the noted societies in the 20s of the 19th century, when the Russian state continued to conduct, the begun in the end of the XVIII century, active policy in the Caucasus in general and in Daghestan, in particular. M.A. Kotzebue attached great importance to the formation of the Jar-Balakan societies, gave information about their composition, number of households, the population and armed forces that they could introduce. The issue of the administrative structure of rural communities and their unions is well covered, administrative officials are listed, their functions of power are shown, as well as the management system of the union as a whole, headed by the Jar Society. Detailed and well-illustrated are social relations, showing all social strata, their economic and social and legal situation, the forms of dependent and rent relations. The work of M.A. Kotzebue contains information about occupations of the population of the Jaro-Belokan societies, shows the state of farming, cattle breeding, horticulture, viticulture, and the special role of sericulture. Described are domestic crafts, noted is the special development of wool processing. The author writes about trade, especially developed with Georgia. Very interesting is the question of the reasons for the leading role of the Jar society, in the coverage of which such reasons were traced: good geographical and strategic position of Jar and other villages of the union, natural conditions that contributed to its special place. The analysis of the information from the works of M.A. Kotzebue, their comparison with similar data from the works of other authors, proves high degree reliability, which makes his work a trustworthy source for researchers dealing with the history of the late Middle Ages.
Keywords: M.A. Kotzebue; Jar-Balakan societies; Jar; formation of the union; administrative structure; farming; cattle breeding; viticulture; silkworm breeding; processing of wool; trade